The Effects of Single Cutting Tool Geometry on Surface Roughness / Rosdi Mohammad...[et al.] - Mohammad, Rosdi; Mohd Ariffin, Mohd Kharul Anuar; Baharuddin, B. T. Hang Tuah; Mustapha, Faizal; Aoyama, Hideki (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This paper aims to optimize a new cutter design for turning of AISI 12L14 material with a Titanium Aluminium Nitride (TiAlN) coated tungsten carbide tools. The interaction of the tool geometry and workpiece on a performance characteristics of surface roughness has been investigated, and Taguchi Orthogonal Array (OA) L9 is selected as the technique for the optimization. In this study, results showed that altering the rake angle of -10 , 0 to +10 rake angles will give significant influence on part’s surface finishing. However, the minor cutting tool edge, Kr2 with 3o is found to be the predominant factor in influencing surface roughness, Ry. The experimental results showed the obtained surface roughness (Ry) values were low, i.e. between 6.76m to 16.18m, and within a desirable range in manufacturing requirements. The optimum turning operation was obtained at T9 test setting with Kr1: 60, Kr2: 3, rake angle: 0, and inclination angle: +3; which provided the smallest surface roughness (Ry) value of 6.76m. It is suggested that the Taguchi parameter design and Taguchi signal-to-noise (S/N ratio) used for the tool optimization is simple, systematic, reliable, and efficient tools for the optimization process in turning.